INFLUENCE OF DISMANTLING COMPANIES ON ENFORCEMENT OF END-OF-LIFE VEHICLE RECYCLING LAW - YAMAGUCHI, Kentaro; KANAYA, Ken (ENVIRONMENTAL SYSTEMS RESEARCH, 2007)
Purpose of this research is to clear influence of dismantling companies on enforcement of end-of-life vehicle recycling law. Method of this research is questionnaire surveyto 300 dismantling companies in Kansai area. Findings of this research are as follows: 1. In dismantling companies more than a half, end-of-life vehicles decrease, and office work and economic burden increase. 2. Automobile auction is related to the reason to which end-of-life vehicles decrease.